FALL OF MOSUL TO ISIS: JOSTLE OF NARRATIVES BETWEEN CONSPIRACY THEORY AND BETRAYAL - Al Hashimi, Hamied; Alzghwabi, Moh Arak (UI Scholars Hub, 2024)
This article examines the rise and conflict of narratives about the fall of the Iraqi city of Mosul to the Islamic State (ISIS), which marks its tenth anniversary this year (2024). ISIS occupied parts of Iraq from 2014 to 2017, and its defeat required Iraqi mobilization and international support from the international coalition. This article attempts to trace the narratives and their conflicts about the main cause of Mosul’s fall to ISIS. The fall of Mosul was like a snowball that rolled and grew, as it spread to a large area of Northwestern Iraq. It has been shown that several factors combined to cause the fall of Mosul, not a single cause. In addition, accusations still exist between the political parties responsible for Mosul's security and administration.